2008
DOI: 10.1093/ije/dyn160
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol poisoning is a main determinant of recent mortality trends in Russia: evidence from a detailed analysis of mortality statistics and autopsies

Abstract: The increases in mortality in 1991-94 and in 1998-2003 coincided with economic and societal crisis, while decreases in 1994-98 and 2003-06 correlate with improvement in the economic situation. Excessive alcohol intake is a major cause of premature male Russian mortality, although many alcohol-related deaths are wrongly attributed to diseases of the circulatory system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
120
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 13 publications
6
120
0
5
Order By: Relevance
“…Similar findings were reported in a more recent population-based study which assessed daily variations in ambulance calls for CVD in Arkhangelsk in 2000-2008 [18]. There was a significant daily variation in calls for CVD in men and women aged 18-59, with increased numbers of calls on weekends and Mondays.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…Similar findings were reported in a more recent population-based study which assessed daily variations in ambulance calls for CVD in Arkhangelsk in 2000-2008 [18]. There was a significant daily variation in calls for CVD in men and women aged 18-59, with increased numbers of calls on weekends and Mondays.…”
supporting
confidence: 86%
“…Cardiovascular diagnoses were even more strongly associated with alcohol in women: acute myocardial infarction (RR=2.04;CI:1.59-2.61), acute ischemic heart disease other than myocardial infarction (RR=9.29;CI:7.97-10.74), chronic ischemic heart disease (RR=2.58;CI:2.09-3.18) and stroke (RR=1.62;CI:1.37-1.93). It was also reported that acute ischemic heart disease other than myocardial infarction includes same misclassified deaths that were actually from alcohol poisoning and was the largest single contributor to the alcohol-associated excess mortality [12].A prospective cohort study of 1966 men and 1738 women performed in Arkhangelsk in 1999-2000 reported a significant dose-response association between hazardous alcohol consumption and the risk of cardiovascular death in women [13]. Women reporting a consumption of 80g alcohol or more at least monthly and a consumption of 5 alcohol units or more on one drinking episode had higher risk of cardiovascular death than abstainers (RR was 5.06;CI:1.54-16.7 and 3.21:CI:1.07-9.58, respectively).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of nearly 25,000 autopsies conducted in Barnaul (Siberia) between 1990-2004 indicated that 21 per cent of all autopsied adult male deaths attributed to circulatory diseases had lethal or near-lethal levels of ethanol concentration in the blood (Zaridze et al 2009a). A further study of 48,000 deaths in three Siberian cities led the authors to conclude that alcohol consumption may be responsible for more than half of all adult male deaths in Russia from 1990 to 2001, and one-third of adult female deaths (Zaridze et al 2009b).…”
Section: Did Russians Drink Themselves To Death?mentioning
confidence: 99%